The student evaluation of teaching: its failure as a research program, and as an administrative guide - Robert Sproule; Călin Vâlsan (Amfiteatru Economic Journal, 2009)
This paper points up the methodological inadequacy of the "student evaluation of teaching" as a research program. We do this by reference to three, interrelated arguments. The first is that the student evaluation of teaching cannot claim to capture the wisdom of a crowd because, as a research program, it fails to meet Surowiecki's conditions for the existence and articulation of the wisdom of a crowd. The second argument extends the first, by stating: (a) the "student evaluation of teaching" research program fails to provide the methodological controls needed to differentiate cause from effect, or put differently (b) the methodological underpinnings of this research program is tantamount to the misapplication of a closed-system paradigm to an open social system. The third argument has two parts. These are that this research program is predicated on: (a) a false analogy between the workings of a business and a university, and therefore (b) on a mischaracterization of the student-professor relationship. These three arguments, these three failures, suggest that the "student evaluation of teaching" research program is methodologically ill-conceived and incoherent, and therefore cannot, with any credulity, serve as a guide to the administration and governance of a university.
Keywords: A2; H83; I23; L3; 330; Student evaluation of teaching; validity; biases; fallacies